Land Suitability of Wani Fruit (Mangifera caesia) for Fruit Development in Mount Batur, Kintamani, Bali - Yuniti, I Gusti Ayu Diah; Sasmita, Nanang; Purba, Jhon Hardy; Komara, Liris Lis (Green Engineering Society, 2024)
Bali Province is one of the local mango producers, namely Wani fruit. Wani fruit (Mangifera caesia) is a local Balinese fruit that has the potential to be developed. Wani fruit production in Bali has decreased due to fewer trees in community gardens. This study aims to determine the suitability of land for wani fruit plants on the slopes of Mount Batur Kintamani. Evaluation of land based on agroecological zones includes slope, drainage, humidity and temperature. Sampling used composite sampling based on agroecological zones and data analysis using descriptive and comparative methods. The results of research on the suitability of Wani fruit land in Kintamani show three classes, namely moderately suitable (CS), marginally suitable (SM), and not suitable (TS) with the main limiting factors being slope, texture, temperature, effective depth and rainfall. Based on the results of research on the Kintamani area, Mount Batur is suitable for the development of Wani Fruit in Bali. Primarily for Horticultural and Conservation purposes for the protection of local species. Based on agroecological zones, the land area in the Kintamani Bali area that can be developed for Wani fruit plants are zones I, II and III with an area of 21,476 Ha, which is 58.53% of the area of Kintamani. The distribution of agroecological zones suitable for the development of Wani fruit in zone I and II land units is predominantly spread in residential plain areas, and land units in zone III are spread in hilly areas.